ANALYSIS OF INVESTMENTS IN THE BUILDING OF THE GELORA BUNG TOMO CITY OF SURABAYA - Sulistianto, Leo Agus; Witjaksana, Budi; Wulandari, Esti (Transpublika Publisher, 2024)
The Gelora Bung Tomo area currently includes a football stadium, three training fields, a wheel-shoe track, a motorcycle racing circuit, and a multipurpose indoor sports building. With the evolving automotive industry, upgrading the circuit from grade D to grade C is necessary to accommodate more races. This involves extending the 650-meter road race track to 1700 meters, including a pit stop area, audience tribune, paddock, and commercial area. The study evaluates the current facilities of the Gelora Bung Tomo (GBT) area in Surabaya and conducts investment analysis to determine financial viability. The research methodology combines quantitative and qualitative approaches using previously obtained primary and secondary data, then compiles cash flow projections and performs investment analysis using investment valuation methods, namely net present value (NPV), internal rate of return (IRR), benefit cost ratio (BCR), and payback period (PP). Based on the results of the analysis with the Net Present Value (NPV) method, if a positive value of Rp. 13.339.690.346 is obtained, then the investment is acceptable. If the benefit-cost ratio is greater than 1,1849, then the project is accepted, and the PP is 30.98 under the time of the investment of 50 years, but the greater the risk faced, the more the overall investment is worthy of being implemented.